Transcriptome and toxin family analysis of the paralysis tick, Ixodes holocyclus - Rodriguez-Valle, M.; Moolhuijzen, Paula; Barrero, R.; Ong, C.; Busch, G.; Karbanowicz, T.; Booth, M.; Clark, R.; Koehbach, J.; Ijaz, H.; Broady, K.; Agnew, K.; et al. (Elsevier, 2017)
© 2017 Australian Society for Parasitology. The Australian paralysis tick (Ixodes holocyclus) secretes neuropathic toxins into saliva that induce host paralysis. Salivary glands and viscera were dissected from fully engorged female I. holocyclus ticks collected from dogs and cats with paralysis symptoms. cDNA from both tissue samples were sequenced using Illumina HiSeq 100bp pair end read technologies. Unique and non-redundant holocyclotoxin sequences were designated as HT2-HT19, as none were identical to the previously described HT1. Specific binding to rat synaptosomes was determined for synthetic HTs, and their neurotoxic capacity was determined by neonatal mouse assay. They induced a powerful paralysis in neonatal mice, particularly HT4 which produced rapid and strong respiratory distress in all animals tested. This is the first known genomic database developed for the Australian paralysis tick. The database contributed to the identification and subsequent characterization of the holocyclotoxin family that will inform the development of novel anti-paralysis control methods.